2010
DOI: 10.1007/s12149-010-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of gated CT acquisition for the quantitative improvement of the gated PET/CT in moving phantom

Abstract: In respiratory motion, PET acquisition in the static mode underestimated the radioactivity and overestimated the dimensions. Neither SCT nor ACT improved these errors. Although PET acquisition in the gated mode improved the quantification of PET/CT images, the additional gated CT acquisition using 4DCT is required for further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the histograms, the peaks were broad and unclear because of the smearing of radioactivity due to respiratory motion. The peaks could not be separated from each other and thus the resulting CSH curves of the 3 phantoms showed a similar pattern [12,13,17]. In the fractal analysis, the FDs of the HO and HE1 phantoms did not differ from each other and were smaller than that of the HE2 phantom.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the histograms, the peaks were broad and unclear because of the smearing of radioactivity due to respiratory motion. The peaks could not be separated from each other and thus the resulting CSH curves of the 3 phantoms showed a similar pattern [12,13,17]. In the fractal analysis, the FDs of the HO and HE1 phantoms did not differ from each other and were smaller than that of the HE2 phantom.…”
Section: Discussionmentioning
confidence: 94%
“…The amplitude of respiratory motion of 2 cm was chosen because the average amplitude of normal free breathing in the cranio-caudal direction was reported to be smaller than 2 cm [16]. In addition, we also selected 2 cm as the amplitude for simulating normal free breathing in our previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory-gated PET imaging is currently expected to improve the quantification of PET [68]. Sakaguchi et al reported that gated imaging acquisition improved the quality of FDG-PET imaging in a moving phantom model [69]. Daouk et al evaluated 48 pulmonary nodules in 43 patients by respiratory-gated PET and ungated method [70].…”
Section: Prospects Of Pet Imaging For Thoracic Cancersmentioning
confidence: 99%